Implementation of Sadd Dzari'ah in The Decision of Religious Courts Class I.B Blora Concerning Marriage Dispensation - Mutakin, Ali; Yani, Ahmad; Muslikaturohmah, Siti (al-'adalah, 2021)
This research aims to analyze the judge's considerations in granting dispensation for child marriage in the Religious Courts Class I.B Blora (the case number 153/Pdt.P/2019/PA.Bla). This research is qualitative using a normative approach. Data were obtained through a review of several case examination documents, books, articles, journals, and regulations related to the research topic. According to the prevailing regulation, the age limit for marriage for both men and women is 19 years. If the man and woman have not reached the specified age, the family is allowed to apply for a marriage dispensation to the Court. This study found that the judge's considerations in deciding the case were based on the concept of sadd al-zari'ah (closing the path of evil). This is because in the case submitted there is two conflicting badness. First, the badness of early marriage relates to the health condition of the prospective bride and groom, which includes the health of reproductive organs, pregnancy, the expected child, and the possibility of a break in the household. Second, the bad impact that arises if the dispensation application was rejected, the two prospective brides continue to be involved in adultery. Of the two bad impacts, adultery is far worse. Based on the sadd al-dzarî'ah, the judge, therefore, granted the dispensation request.